RESPON TANAMAN KEDELAI TERHADAP PEMBERIAN MIKROORGANISME LOKAL (MOL) BONGGOL PISANG DAN PUPUK KANDANG KOTORAN SAPI - Arum Asriyanti Suhastyo; Bondan Hary Setiawan (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2016)
Efforts to increase soybean production can be done by using new varieties and meeting the needs of the nutrient is also one attempt to do. One of fulfillment nutrients by fertilization. The purpose of this study is to examine the effect of banana hump MOL and cow dung manure on the growth and yield of soybean. Research was did in the experimental garden of Polytechnic Banjarnegara. The method was completely randomized design factorial pattern (Split plot). The first factor consisted of three levels of treatment that M0 = without MOL banana hump, M1 = concentration of 2,5 l/ha, M2 = concentration of 5 l/ha. The second factor consists of three levels of treatment that is P0 = without cow manure, P1 = dose of 5 tonnes /ha, P2 = dose of 10 tonnes /ha. Each treatment was repeated three times in order to get 27 experimental plots. Giving MOL banana hump and cow dung manure has not been able to increase the yield and growth of soybean plants. The yield on the dry weight of the plant, number of pods per plant and number of seeds is highest at a concentration of banana hump MOL 5 L ha-1. Cow dung manure dose of 10 tons ha-1 showed the highest yield on plant dry weight, seed number and weight of 100 seeds.